Impact of Quarantine Time in COVID-19 Pandemic Lockdown on Parents and their Children - Abdulkareem, Awayi Ghazy; Qader, Delan Jamal; Ismael, Niyan Hakim; Faris, Gona Othman (Sulaimani Journal for Pure and Applied Sciences, 2021)
On 11 March, 2020, the World Health Organization (WHO) announced the COVID-19 pandemic. In order to respond COVID-19 threat on public health, different countries adopted various social distancing measures and/or locked down their communities completely. As a results of all these measures, global health crisis and other global crises have overlapped. The present cross-sectional quantitative study was aimed at determining the effect of COVID-19 lockdown on parents and their children in the Kurdistan region of Iraq. For this purpose, an online questionnaire-based survey was carried out using a constrictive tool. The study was conducted from the 1st to the 18th of September 2020. The online survey was participated by a total of 1,010 family members. According to the results, 69.5% of the participants were mothers, aged 30 to 39 years, 66.4% were college graduates, and 34.7% gained weight during the lockdown. It was also seen that getting infected, spending a lot of time with electronic devices, stress, and obesity risk have been referred to as the participants’ main concerns.
Keywords: COVID-19; quarantine; impact on children; lockdown; electronic devices